2018
DOI: 10.30878/ces.v25n3a4
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the study of obesity and depression in a sample of Mexican adolescents in northern Mexico

Abstract: The study investigates the prevalence of obesity and depression, and the strength of association between variables in a sample of adolescents in the North of Mexico. A sample of 849 adolescents was evaluated with the Depression Scale for Children. The results showed a high prevalence of depressive symptoms in adolescents who are overweight and obese (57.9%). The Obesity is not related statistically with the Depression rate and no association between variables was found when calculated by gender. The study coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Of those studies that measured depression, the measurement tools also varied across studies. For instance, 3 studies 27 , 28 , 42 used the Center for Epidemiologic Studies Depression Scale in its original or shorter (10 or 7 items, respectively) version; 2 31 , 38 used the Depression Scale for Children, 1 34 used the Depression Inventory for Children, 1 35 used the Zung Scale, 1 36 used Beck's depression inventory, and 1 39 used the Depression Hamilton Anxiety Questionnaire Scale. All these tools were reported as validated among children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those studies that measured depression, the measurement tools also varied across studies. For instance, 3 studies 27 , 28 , 42 used the Center for Epidemiologic Studies Depression Scale in its original or shorter (10 or 7 items, respectively) version; 2 31 , 38 used the Depression Scale for Children, 1 34 used the Depression Inventory for Children, 1 35 used the Zung Scale, 1 36 used Beck's depression inventory, and 1 39 used the Depression Hamilton Anxiety Questionnaire Scale. All these tools were reported as validated among children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In 6 studies, the prevalence of depression was higher among children or adolescents with greater BMIs. 30 , 32–35 , 38 , 42 It was reported that children with overweight or obesity were up to 4.5 times (OR, 4.5; 95%CI, 1.3–14.8; P > 0.008) more likely to report depression. 33 Two studies reported that depression increased when BMI was higher, but such trends were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…The sample was represented mainly by women, which can be attributed to the beauty standards that promote thinness, through the continuous exposure of models with this aesthetic standard. The impact of this "culture of thinness" can produce BID in people, especially women, since they tend to care more about their BI and therefore undergo weight-loss surgery more often to try to "fit" into social beauty standards (44) . In turn, this could explain the high prevalence of BID as measured by the BSQ in the sample and the desire of most of the sample to be thinner, as indicated by the BIA-O.…”
Section: Discussionmentioning
confidence: 99%
“…Como pudo observarse, la muestra fue representada principalmente por mujeres, esto se puede atribuir a parámetros de belleza que están sustentados en promover la delgadez, a través de la continua exposición de modelos con este patrón estético. El impacto de esta "cultura de la delgadez" puede producir en las personas INC, especialmente en las mujeres ya que son quienes se preocupan más por su IC, y por lo tanto se someten a CB con mayor frecuencia para intentar "encajar" en los estándares de belleza sociales (44) . A su vez, esto podría En el modelo propuesto tanto la autoeficacia como la IC resultaron fundamentales para explicar el autocuidado en esta población.…”
Section: Discussionunclassified